Empowering Leadership di Pondok Pesantren: Membentuk Generasi Pemimpin Masa Depan unggul - Zaini, Fawaid (Kariman: Jurnal Pendidikan Keislaman, 2023)
The Islamic boarding school is still often underestimated by society, particularly regarding the non-academic profiles of its graduates, especially in leadership. The purpose of this article is to convey the understanding that Islamic boarding school is not solely focused on Islamic religious education but also serves as an educational institution capable of producing excellent future leaders. This study uses a literature review method, critically examining various relevant sources. Through this literature review, the research finds that the pesantren environment, which emphasizes discipline, responsibility, and cooperation, is an effective platform for training students to become individuals capable of leading and contributing to society. Thus, Islamic boarding school not only produces knowledgeable scholars but also leaders with an empowering leadership style.